THE DEMOCRATIC DECLINE IN INDONESIA UNDER COVID-19 PANDEMIC - Abhipraya, Fairuz Arta; Pahlevi, Moch Edward Trias; Amrurobbi, Azka Abdi (Universitas Padjadjaran, 2020)
The debate about the weakening of democracy in various countries in controlling the COVID-19 pandemic is currently rising. This article aims to describe how the Indonesian government has implemented various pandemic control policies based on the indicators of democracy from the Freedom House, which include transparency, freedom of opinion, human rights, and pluralism. This article uses a qualitative method with a descriptive analysis approach, while data collection uses a literature study focusing on various government efforts and responses from civil society regarding pandemic control. The research results reveal that the policy does not pay attention to the transparency of state budget allocations, including the appointment of goods supplier partners. Threats of doxing against those critical of pandemic control policies interfere with free speech. In the civil society realm, a pandemic’s fear raises the stigma that this virus is identical to the Chinese-ethnic group. This paper concludes that indications of weakening transparency, freedom of opinion, human rights in pandemic control policies, and community responses contrary to pluralism values potentially reduce the quality of democracy in Indonesia.